An Analysis Of Factors Influencing Customer Decisions To Save At BMT NU, Genteng Branch, Banyuwangi - Risky Lukman Azis; Jepri Pangestu; Muhammad Kanzul Fikri (proceedings.icesy, 2026)
This study aims to analyze the factors influencing customers’ decisions to save at Baitul Maal wat Tamwil Nahdlatul Ulama (BMT NU). The research employs a qualitative method with a case study approach at several BMT NU branches. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that trust is the dominant factor influencing saving decisions, stemming from confidence in sharia principles and institutional transparency. Friendly and professional service quality enhances customer comfort, while a fair and transparent profit-sharing system provides a sense of justice. Furthermore, the institution’s religious and socially-oriented image strengthens customer loyalty. In conclusion, customers’ decisions to save at BMT NU are significantly influenced by trust, service quality, profit-sharing system, and institutional image.